2012
DOI: 10.1134/s1063772912040087
|View full text |Cite
|
Sign up to set email alerts
|

Full 3D MHD calculations of accretion flow structure in magnetic cataclysmic variables with strong, complex magnetic fields

Abstract: We have performed three-dimensional magnetohydrodynamical calculations of stream accretion in cataclysmic variable stars for which the white dwarf primary possesses a strong, complex magnetic field. These calculations were motivated by observations of polars: cataclysmic variables containing white dwarfs with magnetic fields sufficiently strong to prevent the formation of an accretion disk. In this case, an accretion stream flows from the L 1 point and impacts directly onto one or more spots on the surface of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Pavlenko (2006) found additional evidence of switching between a dipole spot and an equatorial one, with some drift of an accretion spot in the opposite direction to the WD spin. MHD calculations around the beat cycle were also performed demonstrating the main effects of pole switching in the case of a complex magnetic field structure (Zhilkin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pavlenko (2006) found additional evidence of switching between a dipole spot and an equatorial one, with some drift of an accretion spot in the opposite direction to the WD spin. MHD calculations around the beat cycle were also performed demonstrating the main effects of pole switching in the case of a complex magnetic field structure (Zhilkin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Accretion flows which switch between the one-and two-pole regime has been observed in both QS Tel (Rosen et al 1996) and MT Dra (Schwarz et al 2002). Subsequent studies involving magneto-hydrodynamical simulations, have shown that accretion onto quadrupole Zhilkin et al (2012Zhilkin et al ( , 2016 and octupole Long et al (2012) field topologies are able to produce flows with multiple polar impact zones, or even azimuthally extended hot spots near the WD equator. There is also strong evidence from Zeeman-tomography that the WDs in (at least two) Polars are able to generate complex multi-polar field structures (Beuermann et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…[14]). Such varied scenarios can readily be explored using numerical techniques (see for example [15]). Tantalising evidence for multi-polar accretion geometries has also emerged from spectropolarimetric studies: Employing the Zeeman tomography technique developed in [16], it has been shown that, at least 3 polars (EF Eri, BL Hyi and CP Tuc) possess magnetic field structures significantly more complex than simple offset dipoles [17].…”
Section: Introductionmentioning
confidence: 99%